The everyday realities of the multi-dimensional role of the high school community nurse - Downie, Jill; Chapman, Rose; Orb, Angelica; Juliff, D. (Australian Nursing Federation, 2002)
Abstract: The traditional role of the high school based community community health nurse has changed considerably over recent decades. This article describes a qualitative study, in which nine community health nurses from eight different high schools completed a diary of the interventions and events during the course of two working days in order to identify the dimensions of their role. A short demographic questionnaire was also completed by the nurses and included two open- ended questions concerning their main professional issues and concerns. The researchers sought verification of the interpretation of the data through a focus group interview with the high school nurses. Data analysis indicated that the role of the high school community health nurses (CHN) consisted of seven categories. These were provider of clinical care, counsellor/ mediator, advocacy and support, liaison/referral, health promotion/education and resource agent, and professional management and research role. The findings highlight the complex and demanding aspects of the role of the high school nurse and articulate the importance of describing the contribution of such practitioners in to the promotion of health among adolescents. (author abstract)